2022
DOI: 10.1177/15330338221111228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Genetic Aberrations of Plasma Cell Disorders in Thailand Population

Abstract: Multiple myeloma is an incurable malignancy of plasma cells resulting from impaired terminal B cell development. Almost all patients with multiple myeloma eventually have a relapse. Many studies have demonstrated the importance of the various genomic mutations that characterize multiple myeloma as a complex heterogeneous disease. In recent years, next-generation sequencing has been used to identify the genomic mutation landscape and clonal heterogeneity of multiple myeloma. This is the first study, a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…found that DNMT3A is one of the sixty-three identified mutated driver genes in early MM development ( 136 ). In line with this study, a very recent study also reported the presence of a pathogenic DNMT3A mutation in the MGUS stage ( 137 ). Furthermore, the mutation frequency in DNMT3A was shown to increase upon relapse ( 87 ).…”
Section: Aberrant Dna Methylation In MMsupporting
confidence: 88%
“…found that DNMT3A is one of the sixty-three identified mutated driver genes in early MM development ( 136 ). In line with this study, a very recent study also reported the presence of a pathogenic DNMT3A mutation in the MGUS stage ( 137 ). Furthermore, the mutation frequency in DNMT3A was shown to increase upon relapse ( 87 ).…”
Section: Aberrant Dna Methylation In MMsupporting
confidence: 88%
“…The recent research on target NGS detection from Thailand reported different ranks to the above-mentioned study. 13 One study conducted in 40 NDMM patients with 30 target gene sequencing reported the common mutations in Chinese were ATM, CUL4B, IRF4, KRAS, and NRAS. 14 The other study from China examined the unpurified BM samples of 28 target genes and reported the most common gene mutations were NRAS, PRDM1, FAM46C, MYC, CCND1, LTB, DIS3, KRAS, CRBN, DNMT3A, IRF4, and BRAF .…”
Section: Discussionmentioning
confidence: 99%
“…The FAM46C gene was originally identified as mutated in 13% of the cases analysed by Chapman and colleagues in their 2011 parallel sequencing of 38 MM patient genomes/exomes [5]. Later, similar mutation frequencies were confirmed by others using techniques ranging from fluorescence in situ hybridization (FISH) approaches to genetargeted next generation sequencing (NGS) [45][46][47][48][49][50][51][52][53]. Mutation mapping revealed alterations throughout the entire ORF of FAM46C, with an exception in a small portion of the Nterminal region, with most mutations being either indels or missense single nucleotide variations predicted to have a deleterious effect on protein structure/functionality [54], suggesting that FAM46C behaves as a tumour suppressor gene.…”
Section: The Fam46c Gene and Its Mutations In Cancermentioning
confidence: 98%